Prior in-plane damage on the out-of-plane response of masonry infills - Akhoundi sheik hahmad loo, Farhad (2019)
Although the masonry infills are assumed as non-structural elements, their vulnerability during past earthquakes resulted in huge economical costs and life losses. The out-of-plane collapse of the infills is assumed as a common collapse mechanism. One important parameter on the out-of-plane collapse of the infills, is a presence of prior in-plane damage which in the present paper will be studied in detail. In this scope, the main objective of this study is to analyze the out-of-plane experimental behavior of masonry infilled frames that are characteristic of Portuguese buildings and can be seen in other south European countries. In the experimental program, four half-scale specimens were constructed; one reference specimen and three specimens with different prior inplane damage related to the in-plane drifts of 0.3%, 0.5% and 1%. The out-of-plane loading was applied uniformly to the brick infills by means of an airbag to simulate the effect of earthquakes. The results show that presence of prior in-plane damage affects the out-of-plane response of the specimens and a formula was derived to predict the out-of-plane stiffness and resistance of the infills taking into account the effects of prior in-plane damage.